Effects of zinc and influence of Acremonium lolii on growth parameters, chlorophyll a fluorescence and antioxidant enzyme activities of ryegrass (Lolium perenne L. cv Apollo) - Bonnet, M (Journal of experimental botany, 2000)
The effects of zinc on growth, mineral content, chlorophyll a fluorescence, and detoxifying enzyme activity (ascorbate peroxidase (APX), EC 1.11.1.11; superoxide dismutase (SOD), EC 1.15.1.1) of ryegrass infected or not by Acremonium lolii, and treated with nutrient solution containing 0-50 mM ZnSO(4) were studied. The introduction of zinc induces stress with a decrease in growth at 1, 5 and 10 mM ZnSO(4) and a cessation of growth at 50 mM ZnSO(4), in ryegrass plants infected by A. lolii or not. This decrease in growth may be due to an accumulation of zinc in leaves. Nevertheless, symbiotic plants showed higher values in tiller number, an advantage conferred by the fungus. After 24 d of Zn exposure, leaf fresh weights and leaf water content were lower in plants growing with Zn in the culture medium and no advantage was conferred by the fungus to its host. An increase in Zn supply resulted in a decrease of the Ca, K, Mg, and Cu content of the leaves, a reduction in the quantum yield of electron flow throughout photosystem II (DeltaF/F(1)(m))and a lowering of the efficiency of photosynthetic energy conversion (F(v)/F(m)), compared to control plants. To counter this zinc stress, detoxifying enzymes APX and SOD increased (100%) when Zn reached the value of 50 mM in the nutrient solution. At 10 mM ZnSO(4), the presence of the fungus in the plant led to an increase in the threshold toxicity of plants to zinc by a diminution of APX activity